2019
DOI: 10.1101/756767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA breaks-mediated cost reveals RNase HI as a new target for selectively eliminating antibiotic resistance

Abstract: Antibiotic resistance often causes a fitness cost to bacteria in the absence of the drug. The cost is the main determinant of the prevalence of resistances upon reducing antibiotics use.Understanding its causes is considered the Holy Grail in the antibiotic resistance field. We show that most of the variation in the cost of resistances common in pathogens can be explained by DNA breaks, a previously unsuspected cause. We demonstrate that the cost can be manipulated by targeting the RNase responsible for degrad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The housekeeping nature of the enzymes involved in these synergistic combinations suggests that a wider application for combination therapeutics including RNase HI inhibitors also exists for other organisms. The loss of the rnhC gene in Listeria monocytogenes correlates with a loss of virulence in mice (58), and in E. coli, both streptomycin-resistant strains and rifampicin-resistant strains were competitively disadvantaged in ΔrnhA backgrounds (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The housekeeping nature of the enzymes involved in these synergistic combinations suggests that a wider application for combination therapeutics including RNase HI inhibitors also exists for other organisms. The loss of the rnhC gene in Listeria monocytogenes correlates with a loss of virulence in mice (58), and in E. coli, both streptomycin-resistant strains and rifampicin-resistant strains were competitively disadvantaged in ΔrnhA backgrounds (13).…”
Section: Discussionmentioning
confidence: 99%
“…Cells therefore require precisely controlled levels of RNase HI to prevent dysfunction. Recently it was demonstrated that loss of RNase HI function in E. coli drives the extinction of rifampicin and streptomycinresistant strains (13), suggesting that RNase HI might be a promising new antimicrobial target in light of the current antimicrobial resistance crisis. RNase HI is already a validated target for HIV therapy: Much progress has been made over the last two decades in the discovery and optimisation of inhibitors with different binding modes that are specific and selective to the RNase H activity of HIV-1 RT and that have antiviral activity within cells (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The housekeeping nature of the enzymes involved in these synergistic combinations suggests that a wider application for combination therapeutics including RNase HI inhibitors also exists for other organisms. The loss of the rnhC gene in Listeria monocytogenes correlates with a loss of virulence in mice (58), and in E. coli , both streptomycin-resistant strains and rifampicin-resistant strains were competitively disadvantaged in Δ rnhA backgrounds (13). This indicates the potential for therapeutic aspects of RNase HI inhibition in bacteria even where RNase HI activity is not essential under laboratory conditions, or where rifampicin tolerance is high.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, degeneracy is a main contributor to adaptive flexibility and, in general, to functional robustness and evolvability (583,584). (585). There are a number of key cellular functions that are hyper-protected by, for example, gene redundancy and mutational robustness, with stronger selection for reduced costs of transcriptional-translational errors (586).…”
Section: Evolutionary Trajectories Of Antibiotic Resistance Genes the Gene Space Of Variationmentioning
confidence: 99%
“…This is, however, a highly unlikely outcome; there is a balancing selection in heterogenous bacterial populations, recurrent reverse evolution, with heterogeneous fitnesses in fluctuating habitats, different niches and subniches, and different population sizes, promoting the coexistence of sensitive and resistant strains (1239). We can then modify co-selective and antagonistic pleiotropy effects, fitness costs of resistance, and compensatory adaptations (585,1238). The third step is to exploit the epistatic mechanisms (e.g., those influencing membrane biosynthesis and transport) and chaperones creating a method for disrupting the evolution of antibiotic resistance (1240) or restoring susceptibility, altering intrinsic resistance mechanisms (1241,1242).…”
Section: Targeting Restoration Of Susceptibilitymentioning
confidence: 99%